Exploring the Attitudes of Pediatric Oncologists Toward the Use of Laxatives for the Prevention of Constipation in Patients Undergoing Active Treatment: A Canadian Perspective. (1st August 2014) - Essa, Mohammed; Santo, Anelise Espirito; Fleming, Adam; Mitchell, David; Abish, Sharon
<x xml:space="preserve">Abstract</x> Background: Constipation is a common problem in pediatric oncology patients and may lead to significant consequences. There is a paucity of the published literature on the prevention of constipation in this population. The primary purpose of this study was to explore the current practice of pediatric oncologists in preventing constipation in children receiving active chemotherapy treatment, specifically during periods of intensive vincristine therapy. Methods: A Web-based survey of pediatric oncologists and pediatric oncology trainees in Canadian centers was conducted. Results: A 48% response rate was achieved. The majority of physicians had a lower threshold for defining constipation in oncology patients compared with the published literature. More than 90% of the respondents estimated the prevalence of constipation in pediatric oncology patients to be 30% or higher. The majority of respondents prescribed constipation prophylaxis in the presence of one or more of the following factors: history of constipation prior to or during previous phases of therapy, vincristine combined with either narcotics or immobility, multiple vincristine doses per month, spinal cord compression and immobility, and isolated narcotic therapy. Polyethylene glycol 3350, lactulose, and ducosate were the most commonly recommended first-line prophylactic therapies used. Conclusion: Constipation is a significant problem in patients during cancer treatment. Most oncologists suggest giving laxatives as prophylaxis in the presence of risk factors, as well as prompt treatment once any symptoms appear. Our results suggest a role for the introduction of guidelines in the prevention of constipation, especially for patients receiving frequent vincristine therapy.